2014
DOI: 10.1021/ol5003219
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Enantioselective Formal Hydroamination of Oxa- and Azabicyclic Alkenes with Hydrosilanes and Hydroxylamines

Abstract: A CuCl/(R,R)-Ph-BPE-catalyzed enantioselective formal hydroamination of oxa- and azabicyclic alkenes with polymethylhydrosiloxane (PMHS) and O-benzoylhydroxylamines has been developed. The efficient and stereoselective net addition of hydrogen and nitrogen atoms provides the corresponding optically active oxa- and azanorbornenyl- and -norbornanylamines in good yields and good enantiomeric ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 80 publications
0
43
0
1
Order By: Relevance
“…[37] This transformation was also applicable for oxa-and azabicyclic alkenes [38] and alkenyl dan boronates. [37] This transformation was also applicable for oxa-and azabicyclic alkenes [38] and alkenyl dan boronates.…”
Section: Cu-h Catalyzed Hydroaminationmentioning
confidence: 99%
“…[37] This transformation was also applicable for oxa-and azabicyclic alkenes [38] and alkenyl dan boronates. [37] This transformation was also applicable for oxa-and azabicyclic alkenes [38] and alkenyl dan boronates.…”
Section: Cu-h Catalyzed Hydroaminationmentioning
confidence: 99%
“…[28] In the reported process, the optimal catalyst was found to be a combination of CuCl and ( R , R )-Ph-BPE (L5). The enantioselectivities obtained ranged from moderate to excellent and a wide range of amine electrophiles, including one derived from the hindered 2,2,6,6-tetramethylpiperidine, could be successfully employed.…”
Section: Copper(i) Hydride-catalyzed Hydroamination – Discovery Smentioning
confidence: 99%
“…In particular, while the reduction of ketone 1 with a catalyst generated from DTBM-SEGPHOS indeed requires a low activation energy (Δ G ‡ ) of 9.9 kcal/mol, the same process is less facile when other commercially available ligands are employed. In particular, the use of a catalyst derived from Ph-BPE ( L2 ), another ligand previously employed in CuH chemistry (20, 34), results in a higher activation energy (Δ G ‡ = 13.6 kcal/mol). Furthermore, calculations suggested that the activation barrier for the hydrocupration of enyne 3 is 1.3 kcal/mol lower than that of ketone 1 with this Ph-BPE-based catalyst, indicating the feasibility of chemoselective enyne hydrocupration in the presence of ketones.…”
mentioning
confidence: 99%